On the mymecophilylous species of plociopterus kraatz (Coleoptera: staphylinidae: Staphylinini) described by E. Wasmann - Chatzimanolis, Stylianos (2016)
Wasmann (1925) described two taxa associated with leafcutter ants (as permanent attine-associated species) that he placed in the Xanthopygina genus Plociopterus Kraatz, P. atticida Wasmann (Fig. 1) and P. goeldii Wasmann (Fig. 2). That seemed odd because the genus Plociopterus has similar natural history to the genus Nordus Blackwelder, i.e., predators of other insects found in rotting mushrooms or fruits (Chatzimanolis 2003), and all other described species of Plociopterus have no association with ants. To clarify the taxonomic status of P. atticida and P. goeldii, we borrowed the type specimens from the Natural History Museum of Maastricht. We report here that neither of these taxa belong in Plociopterus, and both belong in the subtribe Philonthina. So far, six species of Philonthina have been recorded in permanent association with leafcutter ants, three of them belonging to the genus Philonthus Stephens and three of them in the genus Hesperus Fauvel (NavarreteHeredia 2001, 2012). Based on our revision of relevant type material from the Naturhistorisches Museum Wien (NMW) and the generic limits currently applied within Philonthina (Chani-Posse 2014), taxonomic changes are here proposed. Since multiple specimens of the taxa involved in the present study are present in Maastricht (Beuk, personal communication) and Vienna, we designate lectotypes herein.